2004
DOI: 10.1038/sj.onc.1208053
|View full text |Cite
|
Sign up to set email alerts
|

ICBP90, an E2F-1 target, recruits HDAC1 and binds to methyl-CpG through its SRA domain

Abstract: ICBP90, inverted CCAAT box-binding protein of 90 kDa, has been reported as a regulator of topoisomerase IIa expression. We present evidence here that ICBP90 binds to methyl-CpG when at least one symmetrically methylated-CpG dinucleotides is presented as its recognition sequence. A SET and RING finger-associated (SRA) domain accounts for the high binding affinity of ICBP90 for methyl-CpG dinucleotides. This protein constitutes a complex with HDAC1 also via its SRA domain, and bound to methylated promoter region… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

19
315
2
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 279 publications
(337 citation statements)
references
References 23 publications
19
315
2
1
Order By: Relevance
“…Although UHRF1 promoter bears a CpG island, no DNA methylation was found in normal or tumor tissue, excluding the possibility of an epigenetic expression feedback loop. As UHRF1 is a known E2F1 target, 29,45 we also examined E2F1 mRNA expression levels in this sample set. Indeed, a strong relationship was observed between the expression levels of the 2 genes, supporting the concept that UHRF1 regulation is under the control of the pRb/E2F1pathway.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although UHRF1 promoter bears a CpG island, no DNA methylation was found in normal or tumor tissue, excluding the possibility of an epigenetic expression feedback loop. As UHRF1 is a known E2F1 target, 29,45 we also examined E2F1 mRNA expression levels in this sample set. Indeed, a strong relationship was observed between the expression levels of the 2 genes, supporting the concept that UHRF1 regulation is under the control of the pRb/E2F1pathway.…”
Section: Discussionmentioning
confidence: 99%
“…29 UHRF1-knockout mouse embryonic stem cells exhibit significant loss of genomic methylation. 25 The UHRF1 gene is a target for the transcriptional activator E2F1, 29 expression is associated with increased cell proliferation. 30,31 Accumulating evidence suggests that UHRF1 has a putative oncogene function.…”
mentioning
confidence: 99%
“…18 Despite its unknown function, the sequence of this protein is highly conserved through evolution; the human protein has a 91% sequence identity to that of horse, and 82 and 83% similarity to those in rat and mouse, respectively, and 75 and 61% to those in opossum and chicken, respectively. For Q454R encoded by rs11755393, the position is not well conserved through evolution and neither are its surrounding amino acid residues.…”
Section: Variants In Uhrf1bp1 Associate With Sle Y Zhang Et Almentioning
confidence: 99%
“…In this point of view, accumulating evidences have shown that UHRF1 acts as a multi-modular protein involved in the maintenance of the chromatin status and its propagation during cell division. Indeed, UHRF1 binds to methylated DNA and recruits DNA methyltransferase 1 (DNMT1) and histone deacetylase 1 (HDAC1) through the SRA (SET and RING finger Associated) domain [13,[16][17][18][19]. These protein-protein interactions precede S phase entry and could be required for cell cycle progression [10,20].…”
Section: Introductionmentioning
confidence: 99%